Heglovstvo v politologiji Adolfa Bibiča - Lukšič, Igor (Teorija in praksa, 2023)
Bibič encountered Hegel on several levels. He tackled Hegel directly in his PhD dissertation in which he studied the relationship between civil society and the state according to Hegel and Marx. Here he did not stop at the Philosophy of Law, but also tackled the Phenomenology of Spirit, namely, Hegel’s key work for entering the Hegelian way of thinking. In terms of the depth of theoretical elaboration the attachment to Hegel crystallised in the 20th century. The thought that bypasses Hegel’s legacy is shallow, the thought that at least tries to learn from Hegel intends to reach deep. Hegel places the state as the highest form in the development of the human being, the highest in the hierarchy of the forms of existence of the freedom of humanity. For him, politics not only resides in the state, but already begins in a natural and civil society form and, in the state as a global process, it shows its mastery. Slovenian political science is fortunate that its primary founder, Adolf Bibič, decided to base his politics on Hegel.
Keywords: Bibič, Adolf; Civilna družba; Država; Hegel, Georg Wilhelm Friedrich; Heglovstvo; Politične teorije